Core@shell Fe3O4@Mn2+-doped NaYF4:Yb/Tm nanoparticles for triple-modality T1/T2-weighted MRI and NIR-to-NIR upconversion luminescence imaging agents. Issue 60 (1st August 2017) - Luo, Yang; Du, Sinan; Zhang, Wei; Liao, Zhengfang; Zuo, Fang; Yang, Shengtao
Abstract : Core@shell structures of Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm nanoparticles (NPs) were prepared and then used for in vivo NIR to NIR (980 nm to 800 nm) imaging, and as dual-mode T 1 / T 2 -weighted MRI because of the co-existence of Fe3 O4 and Mn 2+ in the NPs. Abstract : Core@shell structures of Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm nanoparticles (NPs) with multifunctional properties were prepared using a hydrothermal route with a seed-growth procedure. The effect of Mn 2+ ions on the phase, shape, and upconversion luminescence (UCL) of Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm NPs was explored using X-ray diffraction, transmission electron microscopy, dynamic light scattering, and photoluminescence spectroscopy. Furthermore, hydrophobic to hydrophilic surface modification of the Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm NPs was achieved by coating the NPs with an amphiphilic polymer (poly(maleic anhydride- alt -1-octadecene) (C18 PMH)) modified with amine-functionalized methyl ether poly(ethylene glycol). Then, the NIR-to-NIR UCL ascribed to the Tm 3+ ions, T 1 -weighted MRI ascribed to the Mn 2+ ions, and T 2 -weighted MRI ascribed to the Fe3 O4 core of the hydrophilic Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm NPs were evaluated. The results indicate that Mn 2+ doping is an effective method to control the size/shape and improve the UCL intensity of Fe3 O4 @Mn 2+ -doped NaYF4 :Yb/Tm NPs, which are promising as imaging agents for NIR-to-NIR UCL and T 1 / T 2 -weighted MRI in biomedical research.